Clinical experience with polygenic risk score in subjects with early cognitive concerns. (31st December 2021) - Sauer, Justin; Ballard, Clive; Gibson, Alex; Daunt, Paula; Pither, Richard
Abstract: Background: There is mounting evidence that lifestyle interventions and behavioural changes play a significant role in maintaining cognition and function, as well as preventing dementia. Consequently, it is important that clinicians confronted with subjects with early cognitive concerns, have appropriate tools available to assist in diagnosis and to facilitate risks management appropriately. The application of polygenic risk score (PRS) tests has the potential to contribute towards management planning and to reduce the burden of testing in subjects with low overall risk. Methods: This retrospective analysis considered the application of geno SCORE TM in a small cohort of patients seen over a six month period in a London Memory Clinic. The test was offered to selected patients in the clinic with MCI not clinically attributable to dementia, or cognitively normal individuals concerned about their risks of dementia. The impact upon clinical management and lifestyle modification was reviewed. geno SCORE, a polygenic risk score algorithm, was developed by Cytox to assess genetic risk for the future development of Late‐Onset Alzheimer's disease (LOAD). Results: Patients receiving the geno SCORE test included those with early MCI, subjective memory complaints and a small number concerned about their risk of dementia. In each case, a medical history was taken and individuals assessed using the Addenbrooke's Cognitive Examination, conducted either in clinic or remotely. geno SCORE polygenic risk score was easy to conduct and well received. The results stimulated individuals at risk of developing LOAD to make lifestyle adjustments and thereby potentially modifying their dementia risk. Conclusions: In this study, the geno SCORE PRS test provided a valuable assessment of genetic risk of individuals most likely to decline cognitively decline towards AD and as such, contributed significantly to clinical management decisions. The ease and effectiveness of home sampling of saliva as source DNA for the PRS test was a major factor and well aligned with the continuing need for remote consultations in the light of COVID‐19 concerns. Further larger‐scale studies to determine the full clinical and associated economic impact of the geno SCORE PRS test are required.